Scientific Dynamics and Research Frontiers of Maqashid al Shariah in Islamic Economics: A VOSviewer-Based Bibliometric Exploration - Fadila Nur Afidah Rizki; Innisa Khofifatul Ummah; Aulia Nur Aini; Bambang Sugeng; Luqman Hakim; Moch. Khoirul Anwar (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the scientific dynamics, intellectual structure, and emerging research frontiers of Maqashid al-Shariah in Islamic Economics through a bibliometric approach. The increasing global development of Islamic economics and the growing integration of maqashid al-shariah into sustainability, ethical finance, and social welfare issues have significantly expanded academic interest in this research domain. However, comprehensive mapping regarding thematic evolution, collaboration networks, and research trends remains limited. This study employed a quantitative bibliometric method combined with a systematic literature review (SLR). Data were collected from the Scopus database using maqashid-related keywords, yielding 192 peer-reviewed publications between 2011 and 2025. The data were analyzed using VOSviewer version 1.6.20 through co-occurrence, co-authorship, co-citation, bibliographic coupling, and overlay and density visualizations. The findings indicate a substantial increase in maqashid al-shariah publications, particularly after 2018, with Malaysia accounting for 58.33% of total publications, followed by Indonesia at 21.88%. The dominant research themes include Islamic banking, Islamic finance, sustainable development, social welfare, ESG, and Islamic social finance. The overlay visualization further reveals the emergence of contemporary topics, including Islamic fintech, the digital economy, and sustainability-oriented Islamic economics. The study concludes that maqashid al-shariah has evolved into an interdisciplinary and globally relevant framework capable of supporting ethical, inclusive, and sustainable economic development.